Malaria situation in Lampung Pesawaran during the COVID-19 pandemic - Tusy Triwahyuni; Siti Haryati; Marwan Nusri (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background : At the time of COVID-19 was determined as a pandemic there are still many infectious diseases that have not been eliminated such as HIV / AIDS, tuberculosis, including malaria. Malaria is an infectious disease that existed long before corona virus or COVID-19 appeared in the world. malaria itself is a parasitic infectious disease plasmodium sp transmitted through the bite of a female Anophelese sp mosquito. The current incidence of malaria cases coincides with the COVID-19 pandemic, which could potentially increase or decrease the incidence of malaria cases.Purpose: To find out the comparison of malaria cases in endemic areas before and during the COVID-19 pandemic in The Hanura Health Center of Lampung Pesawaran Regency 2019-2020.. Method: Comparative research with purposive sampling research techniques with the population of all malaria patients in Puskesmas Hanura Pesawaran Lampung Regency from September 2019 to August 2020. Analyze data using univariate and bivariate..Results : The most cases of malaria based on the age before the COVID-19 pandemic at the age of >15 years amounted to 121 patients (72,9%) and during the COVID-19 pandemic the most at the age of >15 years amounted to 25 patients (61,0%). The most cases of malaria by gender before the COVID-19 pandemic were in 102 male patients (61,4%) and based on gender during the COVID-19 pandemic the most was in men as many as 21 patients (51,2%) . Malaria cases before the COVID-19 pandemic were highest in October 2019 at 55 patients (33,1%) and during the COVID-19 pandemic the highest in March 2020 was 14 patients (34,1%).Conclusion: There is a significant comparison in malaria cases before and during the COVID-19 pandemic with a P value of 0.033.